LE PARADOXE DU CRITIQUE D’ART: LA TENSION ENTRE PATHÉTIQUE ET IRONIE DEVANT LES TABLEAUX TOUCHANTS [PARADOX AS THE CRITIQUE OF ART: TENSION BETWEEN PATHOS AND IRONY OF THE “TOUCHING” PAINTINGS] - Nadège Langbour (Studia Litterarum)
In his Salons, Denis Diderot pays special attention to “touching,” pathetic paintings, and his interest to J.-B. Greuze’s art is evidence to that. When Diderot turns to describe Greuze’s canvases or genre painting of J.-B. Le Prince or P. A. Baudouin, he finds himself within the framework of sentimental rhetoric related at once to the pathos of the painted scene and to the sensations of the viewer. Diderot’s style becomes heterogeneous and has a peculiar fluidity that often conceals tongue-in-cheek ironic comments. This irony is, in the first place, a critical instrument of the “salonist” that allows touch upon some of the technical infelicities of the paintings with sly humor. At the same time, not only paintings become the targets of Diderot’s irony; irony manifests itself in the depiction of pathetic paintings when Diderot himself enters the stage. Diderot appears as a “dicephalus” of a kind, a creature with two heads — at once a spectator and an actor. As a spectator, he is fully immersed in the painting, follows the pathos of the scene and describes it with the help of sentimental rhetoric. As an actor, he is capable to distance himself from the painted scene and becomes “insensitive” as the actor whose principles of acting he explicates in “The Paradox of the Actor.” This latter capacity of the contemplator predetermines ironic comments in his descriptions of pathetic paintings.